Homestay save rent method through consumer self-management of electricity power consumption - Dirman Hanafi; Kamal Khairi Kamaruddin; Hisyam Abdul Rahman; Yudhi Gunardi (Institute of Advanced Engineering and Science, 2020)
The rapid growth in the number of homestays and hotels, competition has increased among them. Homestay that is a relatively newcomer in this business should find the way to become competitive. One way is to make rental fees more affordable. In this paper a method to reduce the homestay rental fees are proposed. This is done by separating the component of the electricity cost from the whole rental fees. Then it requires the consumer to pay their own electricity used and also gives opportunity to them to manage their own electricity used how much they need. This mechanism is implemented by equipping the homestay with the coin kilowatt hour (ckWh) meter. The consumer can plan how much they will use the power since they stay by inserting the certain amount of coin into the ckWh meter. After insert the coin the electricity sources will on and ready to use. The main components of this ckWh meter consist of the Arduino Uno microcontroller as a brain of the device, the coin acceptor where the coin will insert, and kilowatt hour meter. Besides that, it also equipped with liquid-crystal display (LCD) to show the amount of money currently available. The experimental test shows that the device develop work well and can control the used of the electricity related to the amount money that has been inserted.